VALUES OF ANTHROPOMETRIC INDICATORS OF LENGTH AND CIRCUMSTANCES OF CHILDREN IN THE FIRST YEAR OF LIFE - Abdullaeva Мавжуда (International Journal of Scientific Pediatrics, 2023)
Indicators of physical development are anthropometric data, the rate of their change in the process of growth, harmonious development, the ratio of calendar and biological age, constitutional features. Purpose of the study: to study the level of physical development according to the main absolute and relative values of children’s body sizes in the dynamics of the first year of life. Materials and methods of research. The study included 106 young children who were prospectively observed throughout the entire observation period from 1 month to 1 year of life. The studies were carried out in accordance with WHO recommendations for studying the growth and development of children. The girth and length dimensions for children were obtained using a horizontal stadiometer and a centimeter tape. The measurement accuracy for girth dimensions and lengths was ±0.1 cm. Results and Conclusions: heterogeneity in the increase in absolute and relative values of the main anthropometric indicators was revealed; absolute and relative values of anthropometry clearly depend on the period of postnatal life and the gender of the examined children; The presented studies are recommended to be taken into account when interpreting the dynamics of anthropometric indicators of the physical development of children in the dynamics of the first year of life.